Mobile phone addiction and insomnia among college students in China during the COVID-19 pandemic: a moderated mediation model - Wang, Jinfu; Xu, Xue; Zuo, Lijun; Wang, Haiyun; Yang, Guan (Frontiers in Public Health, 2024)
Background: Nowadays, it is widely acknowledged that mobile phone addiction is a risky factor for insomnia symptoms, but to date, people know little about the underlying relationship between them among undergraduates during the COVID-19 pandemic. The purpose of the present study was to examine the potential association between mobile phone addiction and insomnia, as well as the mediating role of social anxiety and the moderating role of physical activity. Methods: Using the Mobile Phone Addiction Tendency Scale, Social Phobia Inventory, Physical Activity Rating Scale and Insomnia Severity Index, 301 eligible college students in China were investigated. For data analysis, descriptive analysis, correlation analysis, moderating effect test, moderating effect test were carried out in turn.The findings revealed a favorable correlation between mobile phone addiction, social anxiety and insomnia, as well as between social anxiety and insomnia. But physical activity was negatively correlated with social anxiety and mobile phone addiction, and social anxiety partially mediated the relationship between mobile phone addiction and insomnia. Additionally, physical activity played a significant moderating effect between mobile phone addiction and social anxiety.This study advances the knowledge of how mobile phone addiction raises the likelihood of experiencing insomnia symptoms, and also implies that upping physical activity level could lessen the harmful impacts from mobile phone addiction.